PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DALAM MENINGKATKAN DAYA TARIK WISATA DI PEMANDIAN KOLAM PENAWAR ATAS KETAPANG BANYUWANGI - Nadiya Lifa Ningrum; Widya Puspa Andika (Jurnal Pariwisata Pesona, 2021)
This research was conducted in Kolam Penawar Atas, Dusun Pancoran, Ketapang, Banyuwangi and aims to identify the supporting and inhibitory factors as well as design strategies in community-based ecotourism development. This study is descriptive and qualitative research. The data collection was conducted by interview, observation, and documentation method. The informants in this study were determined by purposive sampling techniques. Data analysis is using triangulation techniques and SWOT analysis. The results showed that: (1) Supporting factors in development of community-based ecotourism in Kolam Penawar Atas include: natural potential and cultural attractions, Support from Local Government, Community Expectations. While the inhibitory factors are: Community Knowledge, Low Community Participation, Land Ownership (2) Strategies that can be implemented based on SWOT analysis include: S-O strategy: utilizing natural and cultural potential as a tourist attraction and empowering the surrounding community for ecotourism development; W-O strategy: establish pokdarwis to manage tourist attractions, establish cooperation with investor to invest, establish cooperation with the government to conduct promotion activities, and cooperate with travel agent; S-T strategy: create photo spot attraction, innovation to manage the attractions to deal with competition, and develop tourism with the ecotourism-environmentally friendly friendly concept tourism; W-T strategy: provide education or training on tourism to the community, approach and coordinate with the community regarding the system of tourism management and revenue sharing, build and maintain tourist facilities and infrastructure, and optimize promotion activities through social media.